Pengaruh Mutasi dan Beban Kerja Terhadap Kinerja Karyawan BPJS Ketenagakerjaan Kantor Cabang Se-Jawa Barat - Hasna Nuraini; Suroso Suroso; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to identify, analyze, and explain the effects of employee turnover and workload on the performance of employees at BPJS Ketenagakerjaan branch offices in the West Java region. This study employs a quantitative method using multiple linear regression analysis and SPSS 25 as the analytical tool. The target population consists of 318 BPJS Ketenagakerjaan employees throughout West Java, and the sample size is 76 respondents, calculated using the Slovin formula. The research findings indicate that employee turnover has a positive impact on employee performance with a calculated t-value of 4.515, which is significantly higher than the critical value of 1.993. Workload showed a positive effect on employee performance with a calculated t-value of 2.478, which was also significantly higher than the critical value of 1.993. Concurrently, employee turnover and workload exerted a significant influence on employee performance, as evidenced by a calculated F-value of 3.373, which was higher than the critical value of 3.12 at a significance level of 0.040. The coefficient of determination (R²) is 0.085, indicating that the combined effect of employee turnover and workload on employee performance accounts for 8.5%, while the remaining variation is attributed to dominant factors not included in this study.